Policy-driven or market-driven? A new perspective on the development of China’s cruise industry - Tong, Helong; Chen, Shishi; Li, Hua (Frontiers in Marine Science, 2023)
The past 15 years have witnessed the rapid development of China’s cruise industry from scratch and the formation of a policy system in the cruise industry, reflecting the shift of the Chinese government’s attitude towards the cruise industry from wait-and-see, recognition and encouragement to active support. The paper conducts a statistical analysis of 128 policies related to the cruise industry issued by China’s administrative departments at all levels. It is found that the release of policies synchronizes with the development of the cruise industry, with each one providing feedback to the other. The policies do not exhibit a time lag with respect to their effects. The evolution of policy types from macro-level guidance to concrete operation is rapid, with the policy structure gradually improving. In line with current characteristics of the development of China’s cruise industry, the themes of the policies concentrate on five areas: cruise tourism services and products, port construction and development, cruise industry chain expansion, cruise industry environment and cruise industry management. However, there is still a lack of adequate policies to support and guide the industrial upgrading of cruise operation and cruise construction and its green and low-carbon development. In addition, the paper points out the main directions of future policy formulation.